2021
DOI: 10.1213/ane.0000000000005677
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Real-Time Electroencephalogram-Guided Anesthesia-Management Curriculum for Educating Residents: A Single-Center Randomized Controlled Trial

Abstract: BACKGROUND: Different anesthetic drugs and patient factors yield unique electroencephalogram (EEG) patterns. Yet, it is unclear how best to teach trainees to interpret EEG time series data and the corresponding spectral information for intraoperative anesthetic titration, or what effect this might have on outcomes. METHODS: We developed an electronic learning curriculum (ELC) that covered EEG spectrogram interpretation and its use in anesthetic titration. Anesthesiology residents at a single academic center we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Yet, the authors of this meta-analysis concluded their meta-analysis abstract by noting that, related particularly to the four study models listed above, “high clinical heterogeneity limits the inferences from this and any future meta-analyses” [ 108 ] on the effect of processed EEG-based anesthetic titration on postoperative delirium risk. To date, no published studies have examined the effect of anesthetic titration based on EEG alpha power on postoperative delirium risk, although one randomized trial found that anesthetic titration based on maximizing frontal alpha power led to decreased hospital length of stay (an exploratory outcome in this study [ 109 ]). An additional study comparing the effect of anesthetic titration to maximize EEG alpha power vs usual care on delirium outcomes is currently underway, with results expected in 2023 [ 110 , 111 ].…”
Section: Eeg Monitoring For Reducing Postoperative Delirium Riskmentioning
confidence: 99%
“…Yet, the authors of this meta-analysis concluded their meta-analysis abstract by noting that, related particularly to the four study models listed above, “high clinical heterogeneity limits the inferences from this and any future meta-analyses” [ 108 ] on the effect of processed EEG-based anesthetic titration on postoperative delirium risk. To date, no published studies have examined the effect of anesthetic titration based on EEG alpha power on postoperative delirium risk, although one randomized trial found that anesthetic titration based on maximizing frontal alpha power led to decreased hospital length of stay (an exploratory outcome in this study [ 109 ]). An additional study comparing the effect of anesthetic titration to maximize EEG alpha power vs usual care on delirium outcomes is currently underway, with results expected in 2023 [ 110 , 111 ].…”
Section: Eeg Monitoring For Reducing Postoperative Delirium Riskmentioning
confidence: 99%
“…Prior EEG training projects have focused only on training anesthesia residents, 19 interpreting EEG waveforms 20 or delivering didactic lectures without in-person intraoperative teaching, 21 and none have targeted pediatric patients or propofol TIVA specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Prior EEG training projects have focused only on training anesthesia residents, 19 interpreting EEG waveforms 20 or delivering didactic lectures without in‐person intraoperative teaching, 21 and none have targeted pediatric patients or propofol TIVA specifically. We used a combination of didactic teaching sessions, intraoperative decision‐tree algorithms, tables, and one‐on‐one training, as well as verbal and written tests to deliver and evaluate EEG TIVA training in the pediatric setting.…”
Section: Discussionmentioning
confidence: 99%